2003
DOI: 10.2989/16085906.2003.9626555
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and communication change in reducing HIV: is Uganda unique?

Abstract: The clearest example of declines in HIV prevalence and changes in sexual behaviour comes from Uganda. Are there lessons to learn for other countries or is Uganda unique? In this paper, we assess the epidemiological and behavioural data on Uganda comparatively to other African countries and then analyse data from other populations where HIV has declined. In Uganda, HIV prevalence declined from 21% to 9.8% from 1991-1998, there was a reduction in non-regular sexual partners by 65% and greater levels of communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 29 publications
1
50
0
2
Order By: Relevance
“…The respondents often mentioned quick progress of the disease and dying faster as effect of one knowing his/her sero status which may be an expressed form of fear of positive results. It has been shown that fear of positive HIV results may be a barrier to HIV testing (17)(18)(19)(20)(21). Similarly as expected late testing was favoured by having an illness in the last two months suggesting that HIV/AIDS related or similar symptoms may actually influence the decision to undertake a test (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The respondents often mentioned quick progress of the disease and dying faster as effect of one knowing his/her sero status which may be an expressed form of fear of positive results. It has been shown that fear of positive HIV results may be a barrier to HIV testing (17)(18)(19)(20)(21). Similarly as expected late testing was favoured by having an illness in the last two months suggesting that HIV/AIDS related or similar symptoms may actually influence the decision to undertake a test (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Netwerke het teoreties 'n beduidende invloed op gedragsverandering (Low-Beer & Stoneburner, 2003). Tradisioneel was die gesondheidsdeskundige of die gemeenskapsleier die enkele fasiliteerder of bron van inligting.…”
Section: Implikasies Op Gemeenskapsvlakunclassified
“…In Uganda het die voorkoms van VIGS vanaf 20% in 1992 tot 9,8% in 1998 gedaal, met 'n verdere afname tot 6,1% in 2001 (Butcher, 2003:4;Low-Beer & Stoneburner, 2003). Hierdie afname is aan verskeie faktore toegeskryf, maar veral aan die volgende: die toename van volgehoue interpersoonlike kommunikasie op alle gemeenskapsvlakke, primêre gedragsverandering deur onthouding en monogame verhoudings, asook die sorg vir VIGS-lyers.…”
Section: Die Ugandese Konteksunclassified
“…Uganda, Senegal and Thailand have successfully lowered their HIV-infection rates without resorting to surgery. For example, HIV prevalence declined in Uganda by 47% following increased safe-sex education and condom promotion [7]. This 'social vaccine' is available and effective now and does not entail the complications of surgery.…”
Section: More Effective Prevention Strategies Availablementioning
confidence: 99%
“…Campaigns to promote safe-sex behaviors have been shown to accomplish a high rate of infection reduction [7], without the surgical risks and complications of circumcision, and at a much lower cost. For the health community to rush to recommend a program based on incomplete evidence is both premature and ill-advised.…”
mentioning
confidence: 99%